Cycad Aulacaspis Scale, Aulacaspis yasumatsui Takagi (Insecta: Homoptera: Sternorrhyncha: Diaspididae) - Thomas J. Weissling; Forrest W. Howard; Avas B. Hamon (EDIS)
This document is EENY-096, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 1999.